Evaluation of Risk Factors and Clinical Characteristics of Cases with Candidemia Developed in Reanimation Intensive Care Units (Annals of Medical Research, 2021)
Aim: The purpose of this study was to evaluate the risk factors, incidence and mortality rate of candidemic cases in Reanimation Intensive Care Units (ICU).
Keywords: Candidemia; Intensive Care Unit; Risk Factors; Mortality.